من أزمة العقل المسلم إلى أزمة التربية والوجدان والرؤية الحضارية: قراءة في الأبعاد الفكرية لمشروع الإصلاح لدى عبد الحميد أبي سليمان: From the Crisis of the Muslim Mind to the Crisis of Education, Sentiment, and Civilizational Vision: An Analysis of the Intellectual Dimensions of Abu Suleiman’s Reform - بدران بن لحسن (الدراسات الإسلامية, 2023)
This study focuses on Abdul Hamid Abi Suleiman’s reform initiative, aiming to offer an interpretation of the project and assess its intellectual, methodological, educational, and cognitive aspects. To accomplish its objective, the research adopts a content analysis approach, concentrating on Abi Suleiman’s primary works, namely, "The Crisis of the Muslim Mind," The Issue of Methodology in Islamic Thought," and "The Crisis of Education and Conscience," along with other pertinent literature. The findings highlight that Abi Suleiman’s writings illuminate diverse dimensions of the crisis faced by the Muslim Ummah, including methodological and intellectual challenges, emotional and educational aspects, and theoretical and philosophical considerations. He successfully integrated theoretical concepts with practical applications in his reform endeavour, incorporating fieldwork and concrete work. Examining the three aforementioned books underscores Abi Suleiman’s commitment to comprehensively reviewing historical reform efforts. Furthermore, these texts reveal interconnected dimensions within Abi Suleiman’s reform initiative, serving as focal points around which his other literary works orbit